Elucidating the impact of incorporating grapefruit skin seed particles into three-dimensional printed denture base resin on Candida Albicans adhesion and surface roughness - Sulaiman , Mira M; Fatalla, Abdalbseet A; AL-Rawas, Matheel; Abdullah, Johari Y; Yhaya, Mohd F (Journal of Baghdad College of Dentistry, 2025)
Background: Denture stomatitis is a common problem in patients wearing dentures. To improve people's health and prevent infection spread, it is essential to select suitable fillers into the denture base material, which should not only be effective in term of durability and mechanical properties, but also do not exert unfavorable effects on the oral tissue. Objectives: The purpose of this study was to determine the effects of adding grapefruit skin seed particles (GSSPS) at different concentrations on the adhesion of Candida albicans and the surface roughness of Three-Dimensional (3D) printed denture base resin. Materials and Methods: Sixty specimens were digitally printed with 30 disks distributed for the Candida albicans adhesion test and another 30 samples for the surface roughness test. Samples in each test were divided into three groups (n=10) for each GSSPS percentage (0 wt%, 5 wt%, and 7 wt%). Spectrophotometer was chosen to determine the optical density of Candida albicans and profilometer was used to measure surface roughness.  Results: There was significant decrease in both the Candida albicans adhesion and the surface roughness of 3D printed denture base resin after addition of GSSPS. Scanning electron microscopy proved the presence of an evenly distributed GSSPS particles, atomic force microscopy proved the decrease in surface roughness when the concentration of GSSPS increased and energy dispersive X-ray spectroscopy (EDX) showed the presence of new elements. Conclusion: Within the limitation of this study, addition of GSSPs to 3D printed denture base resin has a significant effect on decreasing the adhesion of the Candida albicans and the surface roughness, this leads to decrease the opportunity to present denture stomatitis.